Assessment of Eight Entrepreneurial Personality Dimensions: Validity Evidence of the BEPE Battery - Cuesta, Marcelino; Suárez-Álvarez, Javier; Lozano, Luis M.; García-Cueto, Eduardo; Muñiz, José (Frontiers in Psychology, 2018)
Background. The study of entrepreneurial activity has undergone intense development in recent decades. Traditionally this topic has been addressed from three approaches: economic, sociological and psychological. In the study of enterprising personality, two fundamental perspectives stand out: the use of general personality traits, like the Big Five, and the use of more specific traits related to entrepreneurial spirit, such as self-efficacy, autonomy, innovation, optimism, and others. The objective of this study is to provide validity evidence for a new instrument for measuring eight specific dimensions of entrepreneurial personality (BEPE). Method. The sample was composed of 1,170 adults from the general population (59.9% women). The average age was 42.34 years with a standard deviation of 12.96. Of the sample, 13% were self-employed. Internal factorial structure and reliability of BEPE were examined. The relationships with other variables and the discriminative capacity of the BEPE between different groups of workers were analyzed. Results. First order factor analyses show the essential unidimensionality of each of the eight proposed sub-scales, with factorial weights ranging between 0.341 and 0.825. A second-order factor analysis was carried out, obtaining a general dimension of entrepreneurial personality. With regards to reliability, the eight BEPE sub-scales gave high alpha coefficient values, between 0.825 and 0.899, as did the total battery (0.97). BEPE sub-scales show a high canonical correlation with the Big Five personality factors (.795), and with the sub-scales of the Measure of Entrepreneurial Talents and Abilities questionnaire (.815). Conclusions. The BEPE questionnaire for the evaluation of the eight fundamental specific dimensions of the entrepreneurial personality presents adequate psychometric properties. Its relationships with other measures of personality traits are in line with what is expected. Therefore, the BEPE is a new measurement instrument that can be used with confidence both in the applied field and in research.